NATIONAL MEMORY NARRATIVE IN MULTICULTURAL AREA: THE CASE OF POLES IN SOUTHEASTERN LITHUANIA - Šutinienė, Irena (Sociologija. Mintis ir veiksmas, 2016)
The article presents the analysis of the empirical data collected during qualitative research conducted by the author in Southeastern Lithuania in 2012–2013. The perception of representations of Polish national narrative (monuments and commemorative practices) in the ethnic group of Poles in Southeastern Lithuania is analysed. A relationship between national and local memory is discussed. The tensions between both levels of memory (national and local) emerging due to domination of one national memory narrative in local memory culture are analyzed.
Keywords: national history narrative; local memory; memory culture; Southeastern Lithuania